Qatar : evidence of the Palaeolithic earliest people revealed - Scott-Jackson, J. E. (Archaeopress Archaeology, 2021)
This work, with full text in English and Arabic, synthesises the results of extensive fieldwork by the PADMAC Unit (Kellogg College, Oxford) with diverse historical records and reports of earlier investigations, to tell the story of the long and difficult search to discover the identity of the first people to inhabit the sovereign State of Qatar.